THE YOUNG GENERATION CHARACTERS ENHANCEMENT FROM HISTORICAL EVENTS OF VIETNAM VILLAGE IN GALANG ISLAND - Tomi Arianto; Septriani Septriani (eScience Humanity Journal, 2021)
This study aimed to trace the historical events of Kampung Vietnam related to character education of the young generation on the island of Batam and what values ​​can be taken from the historical events of the Vietnamese Village of Galang Island in developing character education for the millennial generation. Using the concept of ethnocentrism, researchers try to trace historical events and patterns of ethnicity in the Galang community in accepting refugees from Vietnam. The existence of Kampung Vietnam on Galang Island should not only be preserved physically, but also the history of the event itself. The aim is that not only tourism (economic) benefits can be taken, but more important than that are values ​​that are useful for character education for the younger generation. . With the historical events of Kampung Vietnam on the island of Galang, it can help improve the quality of the character education formation process for today's young generation. The values ​​that can be taken from the historical events of the Vietnam Village of Galang Island in building the character of the younger generation include the attitude of nationalism, help, tolerance, and empathy for others.